Western myall groves (Acacia papyrocarpa) determine the fine‐scale distribution of soil Collembola in semi‐arid South Australia. (30th June 2016) - Kwok, Alan. B. C.; Greenslade, Penelope
Abstract: Vegetation can exert a strong influence on the distribution and activity of biotic communities across a broad range of spatial scales, especially in arid and semi‐arid ecosystems. At fine spatial scales, patches created by individual plants can support different faunal and floral communities even at locations distant from the plant. These differences can have profound effects on a range of ecosystem processes, including seed dispersal, nutrient cycling and resource distribution. In semi‐arid Australia, areas surrounding groves of western myall ( Acacia papyrocarpa ) trees are largely devoid of vegetation, being referred to as 'halos'. Here, we investigate the soil‐dwelling Collembola in groves of western myall trees, the surrounding halos and nearby chenopod shrubland. We also investigated whether the abundance of Collembola was influenced by soil depth (0–5 cm layer vs. 6–10 cm layer) in groves. We found that collembolan density was approximately nine times lower and taxonomic richness half that in a halo compared with the grove and chenopod vegetation. Furthermore, analyses at finer taxonomic levels indicate that vegetation patches differed in species composition, with some species restricted to or preferring particular patches. In the grove, we found a higher abundance of Collembola in the 0–5 cm soil layer compared with the 6–10 layer. Our results indicate vegetation patches strongly influence collembolan abundance and species composition in bare patches around western myall. As patches created by vegetation are a common feature of semi‐arid and arid regions, we suspect that these effects are widespread although seldom reported. Furthermore, as Collembola are involved in the decomposition process, Acacia papyrocarpa patches will be influencing nutrient cycling through their effects on the soil biota. Our results also emphasize that comprehensive fauna survey and management of woodland ecosystems need to consider fine‐scale processes.